Strategi Komunikasi dalam Meningkatkan Pelayanan Pelanggan PT. Pos Indonesia di Garut - Arreihan Al Febrian; Ummu Salamah; Rosanti Utami Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Today's customers not only want fast and efficient service, but also a positive experience when interacting with the company. Effective communication, both in person and through digital platforms, is key in delivering service values, policies, and benefits to customers. This study aims to analyze and explain the communication strategies implemented by PT. Pos Indonesia in Garut in improving customer service and facing competition. The method used is qualitative research, the researcher plays the role of the main instrument, with data collection through triangulation. The results of the study show that the communication strategy implemented by PT. Pos Indonesia in Garut to improve customer service is planned, analytical, and involves two-way communication, following a five-step model. Customer identification is carried out by understanding the various services available, and the services provided are well responded to. Message drafting involves field research to obtain information related to the company, as well as utilizing social media to build good relationships with customers. The implementation of the strategy is carried out by involving all employees, who are expected to carry out their duties professionally and create loyalty. Various media, such as Facebook, Twitter, Telegram, Instagram, TikTok, websites, and television, are used to improve relationships with customers.